"Your Justice is Too Slow": Will the ICTR fail Rwanda's rape victims? - Binaifer Nowrojee (United Nations Research Institute for Social Development (UNRISD), 2005)
This paper offers an examination of international justice from the perspective of rape survivors from the Rwandan genocide, and exposes the squandered opportunities that have characterized sexual violence prosecutions over the past decade at the International Criminal Tribunal for Rwanda (ICTR). Throughout the Rwandan genocide, widespread sexual violence, directed predominantly against Tutsi women, occurred in every prefecture. Thousands of women were raped on the streets, at checkpoints, in cultivated plots, in or near government buildings, hospitals, churches, and other places where they sought sanctuary. Women were held individually and in groups as sexual slaves for the purpose of rape. They were raped to death using sharp sticks or other objects. Their dead bodies were often left naked, bloody, and spread-eagled in public view. The hate propaganda before and during the genocide fuelled the sexual violence by demonizing Tutsi women's sexuality. Given the evidence and the crimes that the ICTR is tasked with prosecuting, virtually every defendant coming before this international court should be charged and convicted, where appropriate, for his role in perpetrating these acts, or for command responsibility in not preventing the acts of subordinates. Yet on the tenth anniversary of the Rwandan genocide, the ICTR had handed down 21 sentences: 18 convictions and 3 acquittals. An overwhelming 790 per cent of those judgements contained no rape convictions. More disturbingly, there were double the number of acquittals for rape than there were rape convictions. No rape charges were even brought by the Prosecutor's Office in 770 per cent of those adjudicated cases. If the trend continues, full and fair justice for women victims of the Rwandan genocide appears increasingly unlikely before the ICTR. This paper is based on interviews with Rwandan rape survivors, including some who have testified as witnesses before the ICTR. The first part is an examination of the dismal record of the ICTR Prosecutor's Office in investigating and prosecuting sexual violence crimes. The past decade reveals a lack of political will at the senior management level to integrate sexual violence crimes into a consistently followed prosecution strategy...
Keywords: 330